2020
DOI: 10.3389/fpsyg.2020.01176
|View full text |Cite
|
Sign up to set email alerts
|

Early Post-trauma Interventions in Organizations: A Scoping Review

Abstract: Background In some organizations, traumatic events via direct or indirect exposure are routine experiences. The National Institute for Health and Care Excellence reviews (2005; 2018) of post-traumatic stress disorder management in primary and secondary care did not address early interventions for trauma within emergency response organizations. Aims This scoping review was designed to identify research which evaluates the use of early intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 75 publications
(121 reference statements)
2
52
0
Order By: Relevance
“…During the early weeks of the COVID-19 pandemic, Greenberg ( 2020 ) suggested that “it is imperative that managers of [health-care workers] take measures to protect the mental health of staff.” According to a recent meta-analysis, trauma-exposed organizations, such as health care organizations, should provide rapid support to their staff, implementing early post-trauma interventions. Until the pandemic ceases, health care organizations should consider to implement early interventions based on psychological debriefing that are aimed “to prevent the development of adverse reactions” before they arise (Richins et al, 2020 ). Among these interventions, there are (1) debriefing within a group setting, (2) focusing on narrative construction, and (3) social cohesion to support post-incident recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the early weeks of the COVID-19 pandemic, Greenberg ( 2020 ) suggested that “it is imperative that managers of [health-care workers] take measures to protect the mental health of staff.” According to a recent meta-analysis, trauma-exposed organizations, such as health care organizations, should provide rapid support to their staff, implementing early post-trauma interventions. Until the pandemic ceases, health care organizations should consider to implement early interventions based on psychological debriefing that are aimed “to prevent the development of adverse reactions” before they arise (Richins et al, 2020 ). Among these interventions, there are (1) debriefing within a group setting, (2) focusing on narrative construction, and (3) social cohesion to support post-incident recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Among these interventions, there are (1) debriefing within a group setting, (2) focusing on narrative construction, and (3) social cohesion to support post-incident recovery. In their meta-analysis, Richins et al ( 2020 ) found that those interventions were linked to reduced PTSD symptom severity. Furthermore, leaders play a crucial role in the implementation of these early interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found that peer-support programs are a way to promote mental health literacy and health-seeking behaviors and are effective in reducing stigma (Andersen et al, 2015;Milliard, 2020;Van Hasselt et al, 2019). A scoping review by Richins et al (2020) also found that peer support is important in normalizing emotions and reactions. When offered in a group format, peer support was found to facilitate individual recovery and made for a better experience, thus highlighting the role of social support and social cohesion in the psychological processing of traumatic experiences.…”
Section: Peer-support Programs: Current Evidencementioning
confidence: 99%
“…The response to ongoing high stress should aim to support coping, foster resilience, reduce burnout and reduce the risk of developing mental health difficulties. The following guidance is collated from research, best practice guidelines and expert clinical opinion [3][4][5][6][7].…”
Section: Supporting Hospital Staff During Covid-19: Early Interventionsmentioning
confidence: 99%